Solubilization of Oleic Acid by Myrj 59 Surfactant - Mohd Pauzan, Amira Satirawaty Bt; Aziz, Madzlan (Borneo Journal of Resource Science and Technology, 2016)
Palm oil mill effluent (POME) is one of the sources of contamination in effluent that leads to problems such as clogging in drainpipes and sewer lines. POME discharge consists of high content of free fatty acids (FFAs) as well as high concentration of biochemical oxygen demand (BOD), chemical oxygen demand and suspended solids. FFAs in effluent are not favorable due to low water solubility and resistant to biodegradation when precipitated from effluent and binds to soil limiting their bioavailability to microorganisms for biodegradation. Nonionic surfactants are favorable as hydrocarbon or oil solubilizer because they can perform at low temperatures, has low-foaming characteristics and relatively stable at high temperatures and under harsh chemical conditions. Therefore, there is a need for the usage of surfactant that is biodegradable and at the same time effective at solubilizing FFAs in POME before being released to streams. Thus, FFAs will be kept mobilized and readily available for biodegradation by microorganisms. Oleic acid is a long chain free fatty acid presents as the major fatty acid component (40-52 %w/w) in palm oil. Oleic acid was selected for solubilization by biodegradable nonionic surfactant polyoxyethylene (100) stearate with the commercial name Myrj 59. The solubilizations were conducted with various concentrations of Myrj 59; below, at and above the critical micelle concentration (CMC). The amount solubilized was determined by gas chromatography (GC) using flame ionization detector (FID) technique. The solubilization process was confirmed by characterizing the solubilized oil using Fourier Transform infrared (FTIR) to observe changes in chemical bonds. Highest solubilization was achieved with Myrj 59 solution at above its CMC, solubilizing 516.31 ppm oleic acid. The FTIR spectra showed strong peak at 2927 cm-1 with high intensity suggesting intermolecular hydrogen bonding between oleic acid and ethylene oxide (EO) groups of surfactant.